The impact of environmental leadership on entrepreneurial success : the moderating role of green organizational behavior - Abbas, Ali Abdulhassan; Al Hasnawi, Hussein Hurajah (Penerbit Universiti Kebangsaan Malaysia, 2021)
The research aims at improving the employees' understanding about the moderating effect of green organizational behavior on the relationship between environmental leadership and entrepreneurial success, based for exploring opinions 874 employee, working at General Company for Southern Cement, Iraq. The results supported the hypotheses that entrepreneurial success is positively influenced by each environmental behavior that the leader adopts. The results also proved that the green organizational behavior exerted a positive effect on entrepreneurial success. In addition, the green organizational behavior exhibited a moderating effect on the nature of relationship between environmental leadership and entrepreneurial success. Thus, it can be inferred that this outcome contributes towards the improvement of giving importance to environmental behaviors which a leader should adopt. The research concluded with various insights that could create a great impact and pave the way for a sustainable future with regards to nature of relationship among the variables.